Non-semantic operators of emotions - Rogala, Anna (Papers in Linguistics, 2019)
This work is about specific language units, called non-semantic operators of emotions, which are only aimed at expressing emotional states. Material was collected from vlogs and online comments posted under them. The separated operators were then divided into sets which show their formal and functional properties. This allowed a functional and formal typology of non-semantic operators of emotions to be prepared, which was inspired by Ch. S. Peirce’s theory of signs. This is relevant to Polish linguistics, because most existing typologies only refer to semantic exponents of mental states or are based on syntactical criterion. This typology also highlighted the problematic issue of setting limits for these types of units, especially for onomatopoeia as non-semantic operators. Non-semantic operators of emotions are an important object of research due to the fact that their use is dictated by the conversational rule of economy. Thanks to words like oh, ehh, wow and many others, we can show many emotions with a minimum of effort, emphasizing our attitude to the received message and its sender. Despite their short form and lack of semantic meaning, they have many interesting properties, thus providing a wide field for analysis.